Feasibility Study of Biofuel Incorporated Nanoparticles as Sustainable IC Engine Fuel: Opportunities and Challenges - An overview - Abdullahi Tanko Mohammed; Mohd Farid Muhamad Said; Norazila Othman; Anthony Chukwunonso Opia; Ibham Veza (Automotive Experiences, 2023)
The advent of biofuel as a fossil petroleum substitute has been a revolutionary concept in the realm of combustion, but it lacks some qualities that, if addressed, could improve physio-chemical properties and promote energy sustainability. Recently, introducing nanoparticles (NPs) as an additive in fuel for combustion engines has become an effective practice particularly in the automobile industry, to optimize combustion efficiency and minimize emissions. Previous researchers discovered that adding NPs into biodiesel fuel improved overall engine operation performance. Thus, the objective of the research is to summarize existing research findings on nanoparticles effects on fuel properties and engine performance. The paper investigates biofuels, bio-fuel generation classifications, nano-fuel stability, performance, and limitations, as well as current research on the influence of NPs on combustion fuel properties and engine efficiency. Prior to this, researchers have discovered that employing NPs with appropriate additives and concentrations with optimal solubility significantly reduced emissions. In comparison to basic biofuel, adding CeO2 NPs to biofuel boosted brake thermal efficiency (BTE) for low and high operation by 4.1 and 12.02%, respectively. Carbon II Oxide and unburnt hydrocarbon emissions were reduced by 16.13 and 17.59%, respectively, in comparison to pure biofuel under C20-D80 + CeO2 20 ppm. However, due to the biofuel's oxygen concentration, CO2 and NOx emission reductions were not as significant. The findings indicate that utilizing a single bio-fuel generates minimal effective power, yet by incorporating nanoparticles optimizes the operation. Furthermore, future direction of the related work will be discussed particularly on the potential benefits of incorporating NPs in fuel.